Arboviruses in captive non-human primates from Pará state Amazon - Bernal, Marcella Katheryne Marques; Couceiro, Giselle Almeida; Chiang, Jannifer Oliveira; Chagas, André Antônio Correa das; Sarmento, Vânia Pinto; Monteiro, Lucas Tainã Amorim; Rodrigues, Larissa Pereira; Mota, Ligia Souza Lima Silveira da; Pereira, Washington Luiz Assunção (Seven Editora, 2024)
Investigations on health and the human-animal-environment interrelationship make it possible to record zoonotic etiological agents, such as arboviruses and, in relation to non-human primates (NHP), the Amazon stands out for having a rich diversity of these animals that can be potential hosts for arboviruses. In this aspect, the objective of this study was to evaluate the occurrence of arboviruses in captive NHP in the State of Pará. For this purpose, blood samples from 43 specimens from two sponsoring institutions in the State of Pará were used. The sera were analyzed at the Laboratory of Arbovirology and Hemorrhagic Fevers of the Evandro Chagas Institute, Pará State. The Hemagglutination Inhibition test and neutralization test were used. Of the analyses, 25 (58.14%) were positive for one or more of the 19 arboviruses tested, with 68% (17/25) females and 32% (8/25) males. As a result, 71.43% (20/28) of the animals that shared the same enclosure, and 33.33% (5/15) of those that lived in quarantine were positive. Also, of the 25 seropositive strains for arboviruses, 20 (80%) had monotypic reactions and 12 (48%) heterotypic reactions for flaviviruses. Only one sample presented titration ≥ 1280 for Oropouche arbovirus, and was submitted to the neutralization test, whose Logarithmic Index result of ≥ 1.9 was considered positive, suggesting that this primate has a recent infection. The presence of antibodies to the main arboviruses occurring in the Amazon in NHP, due to the expression of immunity, suggests that these animals were infected by the viruses at some stage of life, and may maintain an enzootic cycle. DOI:https://doi.org/10.56238/sevened2024.007-036